Depression, anxiety and coping strategies among Palestinian university students during political violence: a cross sectional study - Ahmead, Muna; El Sharif, Nuha; Abuiram, Issa; Alshawish, Eman; Dweib, Mohammad (Frontiers in Public Health, 2024)
There are numerous wars and ongoing political violence in Palestine and little is known about they have affected Palestinian undergraduate students' mental health and coping strategies. This study aimed to assess the prevalence of depression, and anxiety symptoms and coping mechanisms among Palestinian university students during the times of current political violence in Palestine after October 7, 2023.A cross-sectional descriptive study design was utilized for a sample of students from 3 universities in Palestine (Al Quds University, Hebron University, and An-Najah University) and 1815 participants responded. Data were collected using self-reported questionnaires, including Hospital Anxiety and Depression Scale (HADS) and Brief COPE scale. Person correlation test, chi-square test, and bivariate analysis were performed to examine the associations between research variablesThe estimated prevalence of depression was 65.9%, and 60.9% for anxiety. The logistic regression showed that students from the Arts Faculty, females, and those with working parents were significantly more likely to experience depression and anxiety symptoms. Also, active coping, emotional support, and humor reduced the likelihood of experiencing depression symptoms, while active coping, positive reframing, humor, and acceptance decreased the likelihood of developing anxiety symptoms. Further, the study found that using religion, self-blame, denial, and behavioral disengagement increased the likelihood of depression symptoms while planning, venting, religion, self-blame, denial, and behavioral disengagement increased the likelihood of anxiety symptoms.The study found that political violence often leads to symptoms of depression and anxiety among undergraduates. Furthermore, the use of maladaptive coping mechanisms increases the likelihood that these symptoms will occur. Providing immediate assistance to university students affected by political violence and conflicts is crucial for their emotional and mental recovery and coping with difficulties.